2019
DOI: 10.1001/jama.2019.5346
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Hormone Therapy

Abstract: Hormone therapy is the most effective treatment for managing menopausal vasomotor symptoms. Hot flashes and night sweats affect approximately 70% of midlife women and may persist for a decade or longer. 1 Bothersome vasomotor symptoms have a significant adverse effect on sleep, daily functioning, and quality of life. Cognitive and mood symptoms often accompany disruptive hot flashes. Although lifestyle changes and nonhormonal options are available, women with frequent, severe vasomotor symptoms may greatly ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 10 publications
0
39
0
1
Order By: Relevance
“…The diminished protective effect of hypothyroidism in women who used MHT is consistent with the results from previous WHI trial arm studies that looked at the effects of MHT on the development of invasive breast cancer. In those studies there was a significantly increased risk in the group who received estrogen (conjugated equine estrogens 0.625 mg) plus 2.5 mg medroxyprogesterone acetate (MPA) after adjusting for confounders [HR 1.96, 95% CI 1.17-3.27] (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The diminished protective effect of hypothyroidism in women who used MHT is consistent with the results from previous WHI trial arm studies that looked at the effects of MHT on the development of invasive breast cancer. In those studies there was a significantly increased risk in the group who received estrogen (conjugated equine estrogens 0.625 mg) plus 2.5 mg medroxyprogesterone acetate (MPA) after adjusting for confounders [HR 1.96, 95% CI 1.17-3.27] (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to initiate or continue MHT involves a careful assessment (11,12) and women´s choice. This decision can be supported by tools that could help identify the appropriate women for MHT or for others therapeutic alternatives (13,14). Several questionnaires have been described to measure the QoL in postmenopausal women (15)(16)(17)(18)(19)(20)(21), but few are easy and fast to handle in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Since osteoporosis risk increases steeply with oestrogen withdrawal at menopause, it stands to reason that oestrogen replacement should first be considered for management of osteoporosis in midlife women. (39) This was the case prior to the epochal WHI study in 2002, which reported that the health risks of menopausal hormone therapy (MHT) outweigh its benefits. (40) In recent years, there has been a reconsideration of the data, leading to a more nuanced view of the complex pattern of risks and benefits of MHT.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Observational studies suggest that benefits outweigh risks for effects on bone, heart, cognition, genitourinary symptoms, sexual function, mood and quality of life. (39) Women without a uterus should receive oestrogen alone. Natural oestrogens administered non-orally in the form of transdermal patches or gels offer advantages such as no increased risk of stroke, venous thromboembolism (VTE) and gallstones through bypassing the first-pass hepatic effect.…”
Section: Before 50 Years Of Age: Oestrogen Replacement Encouragedmentioning
confidence: 99%
See 1 more Smart Citation